Phenotype of striatofugal medium spiny neurons in parkinsonian and dyskinetic nonhuman primates: a call for a reappraisal of the functional organization of the basal ganglia - Nadjar, Agnes; Brotchie, Jonathan M; Guigoni, Celine; Li, Qin; Zhou, Shao-Bo; Wang, Gui-Jie; Ravenscroft, Paula; Georges, François; Crossman, Alan R; Bezard, Erwan (The Journal of neuroscience, 2006)
The classic view of anatomofunctional organization of the basal ganglia is that striatopallidal neurons of the "indirect" pathway express D2 dopamine receptors and corelease enkephalin with GABA, whereas striatopallidal neurons of the "direct" pathway bear D1 dopamine receptors and corelease dynorphin and substance P with GABA. Although many studies have investigated the pathophysiology of the basal ganglia after dopamine denervation and subsequent chronic levodopa (L-dopa) treatment, none has ever considered the possibility of plastic changes leading to profound reorganization and/or biochemical phenotype modifications of medium spiny neurons. Therefore, we studied the phenotype of striatal neurons in four groups of nonhuman primates, including the following: normal, parkinsonian, parkinsonian chronically treated with L-dopa without exhibiting dyskinesia, and parkinsonian chronically treated with L-dopa exhibiting overt dyskinesia. To identify striatal cells projecting to external (indirect) or internal (direct) segments of the globus pallidus, the retrograde tracer cholera toxin subunit B (CTb) was injected stereotaxically into the terminal areas. Using immunohistochemistry techniques, brain sections were double labeled for CTb and dopamine receptors, opioid peptides, or the substance P receptor (NK1). We also used HPLC-RIA to assess opioid levels throughout structures of the basal ganglia. Our results suggest that medium spiny neurons retain their phenotype because no variations were observed in any experimental condition. Therefore, it appears unlikely that dyskinesia is related to a phenotype modification of the striatal neurons. However, this study supports the concept of axonal collateralization of striatofugal cells that project to both globus pallidus pars externa and globus pallidus pars interna. Striatofugal pathways are not as segregated in the primate as previously considered.